THE ROMANIZATION OF SCORDISCIAN POTTERY: (as shown by the example of bowl finds from Viminacium) - Tapavički-Ilić, Milica (Rei Cretariae Romanae Fautorum Acta, 2024)
Within the realm of Viminacium, the famous and much spoken about Roman city in Upper Moesia, more than 13,000 graves have been discovered. The greatest part of them represent typical Roman burials, both inhumations (numbered G-nnn) and cremations (numbered G1-nnn).